Age-Associated Differences in Immunoglobulin G1 (IgG1) and IgG2 Subclass Antibodies to Pneumococcal Polysaccharides following Vaccination - Lottenbach, Kathleen R. (American Society for Microbiology, 1999)
Immunoglobulin G (IgG) subclass antibody responses to pneumococcal vaccines were determined for human subjects in four age groups. The ratios of IgG1/IgG2 antibody concentrations declined with advancing age for all five of the serotypes tested. Protein-conjugate vaccines elicited enhanced IgG antibody responses over plain polysaccharide vaccines in infants but not in adult groups.